Study of Photocatalytic Activity and Properties of Transition Metal Ions Doped Nanocrystalline TiO2 Prepared by Sol-Gel Method - K. S. Siddhapara; D. V. Shah (Advances in Materials Science and Engineering)
Transition metal (Mn, Fe, Co,) doped TiO2 nanoparticles were synthesized by the sol-gel method. All the prepared samples were calcined at different temperatures like 200°C to 800°C and characterized by X-ray diffraction (XRD) and energy dispersive X-ray (EDX) analysis. The studies revealed that transition metal (TM) doped nanoparticles have smaller crystalline size and higher surface area than pure TiO2. Dopant ions in the TiO2 structure caused significant absorption shift into the visible region. The results of photodegradation of formaldehyde in aqueous medium under UV light showed that photocatalytic activity of TiO2 nanoparticles was significantly enhanced by the presence of some transition metal ions. Chemical oxygen demand (COD) of formaldehyde solutions done at regular intervals gave a good idea about mineralization of formaldehyde.